1994
DOI: 10.1111/j.1365-2990.1994.tb01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive cell proliferation and microglia following injury to the rat brain

Abstract: The non-astrocytic cells which proliferate in the rat brain after the induction of an area of necrosis have been characterized and counted by means of combined in vivo bromodeoxyuridine (BrdU) administration and immunohistochemical demonstration of glial fibrillary acid protein (GFAP), vimentin, Ricinus communis agglutinin 120 (RCA-1), Griffonia simplicifolia B4 isolectin (GSI-B4), keratan sulphate (KS), carbonic anhydrase C (CA.C), transferrin (TF) and ferritin. Two days after the injury, 7.5% of the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 40 publications
2
42
1
Order By: Relevance
“…At a cellular level, it has been shown that activated, proliferating microglia appear around the implant site as early as 1-day post implantation [18,21,42]. These activated microglia are thought to gradually diminish both excess fluid and cellular debris 6 -8 days after the implant, although necrotic tissue has been observed up to 42 days later [41,44].…”
Section: Introductionmentioning
confidence: 99%
“…At a cellular level, it has been shown that activated, proliferating microglia appear around the implant site as early as 1-day post implantation [18,21,42]. These activated microglia are thought to gradually diminish both excess fluid and cellular debris 6 -8 days after the implant, although necrotic tissue has been observed up to 42 days later [41,44].…”
Section: Introductionmentioning
confidence: 99%
“…Markers for astrocytes (Chen et al, 1993;Petito et al, 1990), microglia (Giordana et al, 1994;Soriano et al, 1994), and oligodendrocytes (Hattori et al, 1992;Irving et al, 1997;Yam et al, 1997) provide useful indices of the glial responses to ischemia and other types of injury. One characteristic response that has been intensively studied is the activation of glia to form reactive microglia and reactive astrocytes after global and focal ischemia and many other types of brain injury.…”
mentioning
confidence: 99%
“…Our electron microscopic data also did not reveal obvious signs of cell shrinkage and nuclear chromatin condensation, suggesting that 192IgG-saporin exerts its cell-damaging action preferentially by induction of necrosis characterized by swelling and cell rupture. Like most other experimental models (Kaur and Ling, 1990;Gehrmann et al, 1992;Giordana et al, 1994;Gehrmann and Kreutzberg, 1995;for review, see Streit and Kreutzberg, 1988;Kreutzberg, 1996) we could also demonstrate a graded response of microglia to the immunotoxin-induced injury. The marker which has been used throughout the present investigation to identify microglia was an HRP-conjugated lectin (the isolectin B 4 derived from Griffonia simplicifolia), which specifically binds a-D-galactose containing glycoconjugates in their plasma membrane and has been shown to stain selectively rat microglial cells in normal as well as in pathologically altered brains (Streit and Kreutzberg, 1987;Ashwell, 1989;Streit, 1990Streit, , 1995.…”
Section: Discussionmentioning
confidence: 79%
“…The number of microglial cells was strikingly increased at day 7 postlesion. Many other studies documented a graded microglial response to experimental brain injury over the first weeks following mechanical lesions (Graeber et al, 1988;Giordana et al, 1994; for review, see Streit and Kreutzberg, 1987;Leong and Ling, 1992;Kreutzberg, 1996) and excitotoxic lesions (Kaur and Ling, 1990;Marty et al, 1991;Kaur et al, 1992).…”
Section: Discussionmentioning
confidence: 96%